Memoirs of a Spacewoman: Naomi Mitchison's intergalactic education. Issue 12 (1st December 2020) - Maher, Ashley
ABSTRACT: In Memoirs of a Spacewoman (1962), a novel in which a space-traveling communications specialist describes her early training and career progression, Naomi Mitchison reimagines the memoir and Bildungs roman forms to depict an individual who develops not by overcoming hostile environments but by being radically transformed by her surroundings. If the classical Bildungsroman mapped the protagonist's youthful development onto the nation, Mitchison's future fiction memoir tests the novelistic means of representing maturity: there can be no ultimate reconciliation for Mary because the universe is composed of an infinite series of worlds. As Mitchison reworks the structure of the novel of development through what might – against Lukacs's '"bad" infinity' – be called the 'good infinity' of space and the expansive self, she also refigures the role of formal education. Subjective time diverges from historical time in space travel, producing 'time blackouts' that allow Mary and her colleagues to extend their education, along with their lives. Memoir bleeds into research publication, and Mitchison accordingly offers a new representative protagonist: the mature researcher, whose malleability and even self-erasure enable a collectively achieved – and always developing – body of knowledge.